Tunisian Political Climate from Aristocracy to Democracy and Presidential Coup: An Emerging Challenge to the Islamic Movements - Raja Umair; Hafiz Sajid Iqbal Shaikh; Faryal Umbreen (Journal of Islamic Thought and Civilization, 2022)
The popular uprising brought forth change in Tunisian presidential palace during 2011 as it entered a state of liminality while becoming a consolidated democracy from authoritarianism. However, after a decade of democratic transition, only the democratic success story of the Arab Spring is in danger after the decree of Tunisian President. This article aims to highlight that by using Article 80 of the constitution, President has seized more power; and it narrates how it contradicts the constitution and negatively impact on political scenario. Furthermore, this study provides an analysis that how certain regional countries are trying to jeopardize the democratic system. Thus, the Islamic movement of Tunisia has been possessing a lion share on Country’s political arena and is considered as the vanguard of Islamic identity and democratic process since 2011 revolution. Finally, it concludes that amid a lenient policy of Rashid Al-Ghannouchi, the founder of the Movement and speaker of the Parliament, towards Islamic doctrine in Tunisian political arena, coup from Tunisian president. Leadership of Al-Nahdah again playing a vital role to stable political climate through dialogue, but it seems that the situation is still in danger. In this article, the primary and secondary data has been analyzed by using Discourse analysis method with its approach of Critical Discourse Analysis (CDA).